Comparison Between Snowflake Fractal and Koch Fractal for Intelligent Reflecting Surface - Nur Syahirah Mohd Yaziz; M. K. A. Rahim; Noor Asmawati Samsuri; Farid Zubir; Sunti Tuntrakool; Taufiqqurrachman (My University, 2025)
This paper compares two fractal metasurface designs for Intelligent Reflecting Surfaces at X-band which is with a snowflake-shaped fractal ring and a fractal Koch metasurface. The snowflake ring design with a 10GHz center frequency achieves very high reflectance ($\sim 90 {\%}$) at resonance and a bandwidth of about 1.90 GHz. The Koch-fractal design response with a bandwidth of 2.10 GHz at a center frequency of 10GHz. The method for both fractal metasurfaces and a comparable on their reflection coefficients, phase behaviour, bandwidth and current distributions are discussed in section II and section III.
Keywords: Advanced Antenna and Metasurface Technologies; Metamaterials and Metasurfaces Applications; Advanced Wireless Communication Technologies